2006
DOI: 10.1007/s12020-006-0017-0
|View full text |Cite
|
Sign up to set email alerts
|

The predictive value of CTLA-4 and Tg polymorphisms in the recurrence of graves’ disease after antithyroid withdrawal

Abstract: Graves' disease (GD) is a multifactorial disease that develops as a result of complex interactions between genetic and environmental factors. The aim of our study is to determine the frequency of cytotoxic T-lymphocyte- associated antigen-4 (CTLA-4) A/G and TG C/T exon 33 SNPs (Tg E33SNP) in GD and to evaluate the relation between recurrence and these polymorphisms. A total of 187 subjects, including 97 previously treated GD patients and 90 age and gender matched control subjects were studied. We examined the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…This situation might be multifactorial, including the larger goiter sizes of patients with Gravesʼ disease, the geographical difference in iodine consumption, the strict inclusion criteria as well as the ethnic and genetic background of the study population. For instance, while CTLA4-49 polymorphism was not associated with relapse in the original study of Vos et al [6], it was suggested as a risk factor for relapse in Turkish patients with GD [15]. However, there is no study so far to explain the exact cause of the high number of poorly controlled cases during ATD treatment in our country.…”
Section: Discussionmentioning
confidence: 66%
“…This situation might be multifactorial, including the larger goiter sizes of patients with Gravesʼ disease, the geographical difference in iodine consumption, the strict inclusion criteria as well as the ethnic and genetic background of the study population. For instance, while CTLA4-49 polymorphism was not associated with relapse in the original study of Vos et al [6], it was suggested as a risk factor for relapse in Turkish patients with GD [15]. However, there is no study so far to explain the exact cause of the high number of poorly controlled cases during ATD treatment in our country.…”
Section: Discussionmentioning
confidence: 66%
“…The results of our research suggested that some of the alleles, genotypes and haplotypes of the five SNPs in BTLA gene are associated with the risk, development and prognosis of breast cancer. The immunoinhibitory receptors, CTLA-4, PD-1 and BTLA, can regulate the lymphocyte activation, so these molecules become ideal candidate genes in case-control relationship studies between the gene polymorphisms and the risk of autoimmune diseases and cancer in recent years [14][15][16][17]. In this report, we provided the first evidence that BTLA gene polymorphisms were associated with the breast cancer susceptibility in Chinese population.…”
Section: Discussionmentioning
confidence: 98%
“…1 according to suggestions of the PRISMA group (7)). Of these, 375 fulltext articles were assessed for eligibility and 54 trials were included in the final data analysis (9,10,11,12,13,14,15,16,17,18,19,20,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49 Tables 1 and 2). Of note, the number of patients does not add up to the grand total as data reported were both used for the genomic data table and the quantitative analysis.…”
Section: Study Selection and Study Characteristicsmentioning
confidence: 99%